Nutrition status of female winter sports athletes - Jiménez-Casquet, M. J.; Conde-Pipó, J.; Valenzuela-Barranco, I.; Rienda-Contreras, R.; Olea-Serrano, F.; Bouzas, C.; Tur, J. A.; Mariscal-Arcas, M. (Nutrients, 2023)
Eating disorders, especially restrictive eating, are common among female athletes. There are two main types of winter sports: those that are practiced outdoors on snow (-25 to +5 °C and 2500 m), such as alpine skiing and snowboarding, and those that are practiced indoors on ice (5-10 °C at low altitude), such as figure skating and ice hockey. The aim of this research was to identify the nutritional status and potential risk of female athletes practicing winter sports, considering the altitude of training. The sample was composed of 58 women (aged 19.81 years (SD: 12.61)) who were competitors in some winter sports. Anthropometrics and nutritional variables were taken. Statistically significant differences were found between HA and LA groups for all the characteristics except thigh skinfold, and neither group had an energy intake (EI) that matched their total energy expenditure (TEE). Both groups met at least two-thirds of the RDI for all minerals and vitamins except iodine, fluorine, vitamin D, vitamin E, and retinol. This study suggests that female winter sports athletes have insufficient energy, vitamin, and mineral intake, which can be worsened with altitude.